Role of Sonographic Imaging Findings in Evaluation of Cases Presenting with History of Blunt Abdominal Trauma in UCMS-TH - Rawal, Sanju; Mukhi, Sadhan (Journal of Universal College of Medical Sciences, 2020)
INTRODUCTION Physical examination is often unreliable. Computed tomography scan is costly, time consuming, requires injection of contrast, exposure to radiation and patient transport thereby limiting its use. With the usage of sonography, it is possible to evaluate and help in the management of patients with blunt abdominal trauma. The proposed study enables sonographic technique in assessing and accurately detecting the presence of free fluid and to pin point the injured organ, thereby helping the clinicians and surgeons in appropriate management MATERIAL AND METHODS Our study was cross sectional conducted on UCMS-TH, Bhairahawa, Nepal. Total 150 cases with history of blunt abdominal trauma were included and scanned by GE LOGIQ6 PRO ultrasound scanner for the duration of one year. RESULTS A total of 150 patients were evaluated 121 were males and 29 were females. Free fluid was detected in total 112 cases (74.66%) out of which with most common injured solid organs were Liver and spleen in total 31 cases (20.7%) each, which were further confirmed on CT scan. CONCLUSION Ultrasonography is easy to perform, quick, cost effective and is highly sensitive in detecting free fluid and solid organ injuries however insignificant in patients with bowel or mesenteric injuries in cases of blunt abdominal trauma and demand CT scan.